1989
DOI: 10.1111/j.1365-2389.1989.tb01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction kinetics of the adsorption and desorption of nickel, zinc and cadmium by goethite. II Modelling the extent and rate of reaction

Abstract: A model of the reaction of metal ions with a variable charge surface was modified and applied to goethite that had been formed in the presence of silicate. The data included the effects of initial concentrations of Ni, Zn and Cd ranging from 1 to 100 p~, of periods from 2 h to 42 d, of temperatures from 5 to 35"C, of pH from about 4 to about 8, and of background electrolyte from 0.01 to 1.0 M.The observed effects of concentration and pH were explained by assuming that the reacting surface sites were heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 26 publications
5
53
0
Order By: Relevance
“…This was due to the reduction in the metal repulsion by the positively charged surface, in consequence of the oxide removal (Silveira et al, 2002). For pH close to 7.0, practically all added Ni was adsorbed, corroborating results obtained by several authors that also observed drastic increase in the metal adsorption when soil pH were raised above 7.0 (Harter, 1979;Barrow et al, 1989;McBride, 1989;Schulthess & Huang, 1990;Scheidegger et al, 1996;Mellis & Casagrande, 2001 (Rodela et al, 2002). Therefore, even for the higher pH values tested in this research, the possibility of finding Ni in the form Ni(OH) 2 0 was very low.…”
Section: Resultssupporting
confidence: 76%
“…This was due to the reduction in the metal repulsion by the positively charged surface, in consequence of the oxide removal (Silveira et al, 2002). For pH close to 7.0, practically all added Ni was adsorbed, corroborating results obtained by several authors that also observed drastic increase in the metal adsorption when soil pH were raised above 7.0 (Harter, 1979;Barrow et al, 1989;McBride, 1989;Schulthess & Huang, 1990;Scheidegger et al, 1996;Mellis & Casagrande, 2001 (Rodela et al, 2002). Therefore, even for the higher pH values tested in this research, the possibility of finding Ni in the form Ni(OH) 2 0 was very low.…”
Section: Resultssupporting
confidence: 76%
“…On the other hand, thermodynamic analyses suggest that while transition metals like Zn may be chemically sorbed to goethite (13,14), adsorption to HFO involves physical forces (9,10,13). Long-term studies reveal that intraparticle diffusion is the ratelimiting mechanism for sorption to the microporous oxides, and thus zinc sorption may require from a few months to a few years to reach equilibrium (10,(15)(16)(17). Similar studies with goethite indicate microporosity is not significant (13).…”
Section: Introductionmentioning
confidence: 80%
“…Because of the complexity of metal-particle interactions, two common features of this type of study are single metal-substrate experimental designs, and the use of syntheticallyderived goethite (a-FeOOH), a crystalline Fe oxide (e.g. Ankomah, 1992;Barrow et al, 1989). In natural sediments, however, other oxides such as ferrihydrite and lepidocrocite have been identified (Fortin et al, 1993, which are more amorphous than goethite and consequently may have quite different sorption characteristics (Schwertmann & Cornell, 1991).…”
Section: Introductionmentioning
confidence: 98%